Q. 695.0( 1 Vote )

Fill in the blank

Answer :

A skew symmetric matrix

Let A and B are two skew symmetric matrices.


A’=-A ..(1)


B’=-B ..(2)


Now Let A+B=C ..(3)


C’=(A+B)’=A’+B’


A’+B’=(-A)+(-B)


(-A)+(-B)=-(A+B)=-C


C’=-C (Skew Symmetric matrix)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USMathematics - Exemplar

<span lang="EN-USMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Fill in the blankMathematics - Exemplar

If A, B are squarMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Express the folloMathematics - Board Papers

Fill in the blankMathematics - Exemplar